The European Health Insurance Card, between Benefits and Limitations “Another Piece of Europe in Your Pocket” - Anamaria Groza (Perspectives of Law and Public Administration, 2023)
The European Health Insurance Card was adopted after long and slow procedures, in order to consolidate the internal market. Nowadays, it has become an important piece of the European health policy and of the European identity. The European citizens can have medical benefits in another Member State that the State where they have a medical insurance, benefits that are necessary and in the absence of which, these citizens should end their stay and return to the State of insurance. The medical assistance can be necessary even because of pre-existing or chronic diseases, pregnancy and birth. The European Health Insurance Card cannot be used in case of planned medical assistance. The medical assistance thus received can be free of charge, partially free of charge or not, according to the legislation of each Member State. In contrast to its jurisprudence in the field of planned medical treatments, the European Court of Justice has decided that a partial reimbursement in this case is not contrary to free movement of services.